Teachers’ Pragmatic Strategies in Motivating Elementary School Students to Learn - Harol Hamonangan; Erna Ikawati (Jurnal Hata Poda, 2026)
This study investigates how teachers apply pragmatic strategies to enhance elementary schoolstudents’ learning motivation. Pragmatic strategies are viewed as communicative practices that gobeyond the delivery of lesson content, emphasizing appropriate, contextual, and persuasive languageuse that positively shapes classroom interaction. Using a descriptive qualitative design, data werecollected through observation, interviews, and documentation involving elementary school teachersand students. The results reveal that teachers utilize various pragmatic strategies, including directivespeech acts with persuasive intent, humor to build a relaxed learning atmosphere, and praise orrewards to strengthen motivation. Teachers also adapt their language to students’ developmentallevels and consider their sociocultural contexts. These practices effectively stimulate both intrinsicand extrinsic motivation among students. In conclusion, teachers’ pragmatic competence contributessignificantly to creating supportive classroom environments, fostering enthusiasm for learning, andincreasing student engagement. Developing teachers’ pragmatic awareness is therefore essential tosustaining and enhancing students’ motivation in the learning process.